Politik Identitas Dalam Krisis Ukraina 2013 - Christian H.J De Fretes; Chikitta Carnelian (Cakrawala Jurnal Penelitian Sosial, 2017)
The monetary crisis that happened in Ukraine is not only affected the economic aspect but also politics. Economic instability makes the Ukrainians faced the dilemmatic choices that certainly leads to political consequences. The Ukrainians have to choose between The EU and Russia are the two options owned by as the right solutions. One of the impacts of the Ukrainian policy of choosing Russia as a solution to the crisis is the spread of protests from a pro-EU. This choice turned into violence (riots) and made Ukraine divided into two parts: Crimea and Lviv. Crimea (Eastern Ukraine) which the majority uses Russian language and Lviv (Western Ukraine) who wants to "escape" from Russia and joins the EU. Crimea Referendum is the climax of the conflict in Ukraine, which ended with the decision to separate from the territory of Ukrainian sovereignty and join Russia, voted by the majority of Crimean society. It shows that the Crimean disintegration process is fundamentally happened because there is the domination of primordial issues aside from the competitive situation between EU and Russia. It proves that the politic of identity puts the identity issue as the main instrument in this case.